2014
DOI: 10.1111/hel.12142
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Clinical Isolates of Helicobacter pylori in Pakistan Reveals High Degrees of Pathogenicity and High Frequencies of Antibiotic Resistance

Abstract: Background Antibiotic resistance in Helicobacter pylori contributes to failure in eradicating the infection and is most often due to point and missense mutations in a few key genes. Methods The antibiotic susceptibility profiles of H. pylori isolates from 46 Pakistani patients were determined by Etest. Resistance and pathogenicity genes were amplified, and sequences were analyzed to determine the presence of mutations. Results A high percentage of isolates (73.9%) were resistant to metronidazole (MTZ), wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
42
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 71 publications
8
42
3
Order By: Relevance
“…AMX is one of the most commonly used antibiotics in recent years in Nepal as similar as ceftriaxone and gentamycin [36]. Additionally we observed no resistance to TCN, in contrast to studies from India and Pakistan [22, 32, 35, 37]. TCN is used as a salvage quadruple therapy [28, 38] and may be a useful alternative first-line regimen in Nepal.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…AMX is one of the most commonly used antibiotics in recent years in Nepal as similar as ceftriaxone and gentamycin [36]. Additionally we observed no resistance to TCN, in contrast to studies from India and Pakistan [22, 32, 35, 37]. TCN is used as a salvage quadruple therapy [28, 38] and may be a useful alternative first-line regimen in Nepal.…”
Section: Discussionmentioning
confidence: 49%
“…Together with CAM or MNZ, AMX is the first-line regimen for treatment of H. pylori infection particularly as a secondary antibiotic in the low efficacy of CAM-based triple treatment zone [2831]. Although in general the AMX resistance is rare, the increasing AMX primary resistance rates have been reported in the neighbor’s country; India and Pakistan [22, 3235]. AMX is one of the most commonly used antibiotics in recent years in Nepal as similar as ceftriaxone and gentamycin [36].…”
Section: Discussionmentioning
confidence: 99%
“…Our study demonstrated the distribution of rdxA and frxA mutation sites was random, scattered, and irregular. 39,41 Additionally, some antibiotic-resistant strains have no rdxA mutation, suggesting other resistant mechanisms such as mutation of ferric uptake regulator, overexpression of a DNA repair protein, tolC efflux pump, or Lon protease may also relate with the acquisition of MNZ resistance in H. pylori, [42][43][44][45] which needs further investigation. Molecular docking studies showed there were some sites of those four types relevant with resistant after mutation, for example, 33 and 35 sites of the first type; 58 and 192 of the second type; S45N and Y47C of the third type; M21V/I/A, A118S, and K64N of the forth type.…”
Section: Discussionmentioning
confidence: 99%
“…In H. pylori strains recently isolated from biopsies of 46 patients, 37 (80.4%) of the 46 H. pylori clinical isolates were positive for cagA [40]. Additionally, the cagA gene was mostly accompanied by vacA s1m1 genotype in these isolates.…”
Section: Discussionmentioning
confidence: 94%